Exploring the Co-Teaching Experience in a Graduate-Level, Principal Preparation Course - Jafeth E. Sanchez; Kelly Humphreys; Kevin Carroll (Park University, 2019)
This article presents a case study conducted by three co-instructors (one faculty member and two practicing principals) who examined their experiences co-teaching a newly revised, graduate-level, principal preparation course. Three themes were identified through their experiential stories: strengths of the co-teaching model, supports and needs, and hindrances. These primary themes, along with notable sub-themes are detailed. A discussion on co-teaching as an innovative teaching method in higher education is provided with a particular focus at the graduate level. Implications for practice and suggestions for future research are discussed in light of these unique findings on co-teaching experiences.